High-silicon-carbon-ratio low-alloying gray cast iron material, preparation method thereof and HT350 conjoined cylinder cover casting

By adopting a high silicon-carbon ratio and low alloying process in gray cast iron materials and combining with the incubation and treatment technology, the problem of large shrinkage tendency in the castings in the prior art is solved, and the high mechanical properties and low shrinkage characteristics of the HT350 integrated cylinder head castings are achieved.

CN119843162APending Publication Date: 2025-04-18WEICHAI POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077061.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing high alloying and low carbon equivalent processes increase the mechanical properties of the cylinder head of the diesel engine while increasing the shrinkage tendency of the castings, affecting sealing and stability.

Method used

Using high silicon-carbon ratio, low alloyed gray cast iron material, by adjusting the content of carbon and silicon and the proportion of alloy elements, combined with the secondary incubation treatment during the previous incubation and casting of the furnace, HT350 integrated cylinder head castings with high mechanical properties and low shrinkage tendency were prepared.

Benefits of technology

The tensile strength of the casting reaches more than 300MPa and the hardness reaches 200~250HBW, and the tendency of the casting to shrink and ensure efficient sealing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005247411340000081
    Figure BDA0005247411340000081
  • Figure BDA0005247411340000091
    Figure BDA0005247411340000091
  • Figure HDA0005247411350000011
    Figure HDA0005247411350000011
Patent Text Reader

Abstract

The invention provides a high-silicon-carbon-ratio low-alloying gray cast iron material and a preparation method thereof and an HT350 conjoined cylinder cover casting, and the high-silicon-carbon-ratio low-alloying gray cast iron material comprises the following components in percentage by mass: 3.00-3.25% of C, 2.10-2.50% of Si, 0.6-1.2% of Mn, 0.07% < = S < = 0.13%, 0.06% < = P, 0.3-0.7% of Cu, 0.15-0.30% of Cr, 0.05-0.20% of Mo, 0.03-0.07% of Sn and the balance of Fe. The gray cast iron material composed of the components according to the dosage has the high silicon-carbon ratio and low alloying, and the mechanical property of a casting is improved; the high carbon equivalent reduces the shrinkage tendency of the casting. The conjoined cylinder cover (the wall thickness of a sampling part is 20-30 mm) produced by pouring the gray cast iron material has the advantages that the body tensile strength can reach more than 300 MPa, the hardness reaches 200-250 HBW, and the shrinkage porosity and water leakage rate of a casting is less than 0.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of grey cast iron materials, and in particular relates to a high silicon-carbon ratio low-alloy grey cast iron material and a preparation method thereof, and an HT350 conjoined cylinder head casting. Background Art

[0002] As the explosion pressure of diesel engines continues to increase, the mechanical properties of diesel engine cylinder blocks and cylinder heads are increasingly required, and the material requirement for gray cast iron combined cylinder heads has reached HT350. The cylinder head is an important component of the diesel engine, forming a combustion chamber with the upper part of the cylinder block, and is required to have high strength and sealing. In addition, the combined cylinder head casting has a complex structure, a large variation in wall thickness, and many hot spots.

[0003] The process routes generally used for high-strength gray cast iron are high alloying process or low carbon equivalent process. These two processes can effectively ensure the mechanical properties of castings, but high alloying and low carbon equivalent will lead to an increased shrinkage tendency of castings. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a high silicon-carbon ratio low-alloyed gray cast iron material and a preparation method thereof and an HT350 combined cylinder head casting, wherein the gray cast iron material can ensure that the material of the combined cylinder head meets the HT350 requirements, the tensile strength of the casting body (cylinder head fire surface position) reaches more than 300MPa, the hardness HBW (200-250), and the shrinkage tendency of the casting is reduced.

[0005] The present invention provides a high silicon-carbon ratio low alloy gray cast iron material, which comprises the following components by mass fraction:

[0006] C 3.00%~3.25%, Si 2.10%~2.50%, Mn0.6%~1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%~0.7%, Cr 0.15%~0.30%, Mo 0.05%~0.20%, Sn0.03%~0.07%, and the balance is Fe.

[0007] Preferably, the silicon-carbon ratio is 0.7 to 0.9.

[0008] Preferably, the molten iron carbon equivalent of the cylinder head material is 3.85-4.15%.

[0009] The present invention provides a method for preparing the high silicon-carbon ratio low-alloyed gray cast iron material described in the above technical solution, comprising the following steps:

[0010] The recycled materials are melted, silicon carbide, manganese silicon alloy, and scrap steel are added; the carburizer is added in batches along with the iron materials, and the iron materials include scrap steel and recycled materials;

[0011] When the weight of the iron material (scrap steel and recycled materials) reaches 75-85% of the full furnace, add ferrosilicon and ferrosulfur, as well as electrolytic copper, ferrochrome, ferromolybdenum and tin particles. After all are melted, heat it to 1450-1500℃, sprinkle in the slag remover to remove the slag, and then heat it up and let it stand;

[0012] After standing, the iron is tapped and silicon-barium-calcium inoculants are added. After the inoculation is completed, the molten iron in the ladle is taken to test the chemical composition. After the chemical composition is qualified, pouring is carried out;

[0013] During the pouring process, silicon-zirconium inoculant is added to perform secondary inoculation to obtain a cast casting, which is then cooled to obtain a low-alloy gray cast iron material with a high silicon-carbon ratio.

[0014] Preferably, the chemical composition of the molten iron after standing is: C 3.00%-3.25%, Si 1.80%-2.00%, Mn0.6%-1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%-0.7%, Cr 0.15%-0.30%, Mo0.05%-0.20%, Sn 0.03%-0.07%.

[0015] Preferably, the particle size of the silicon-barium-calcium inoculant is 2 to 8 mm;

[0016] The particle size of the silicon-zirconium inoculant is 0.15-0.7 mm.

[0017] Preferably, the temperature is raised to 1530-1550° C. and then allowed to stand;

[0018] The standing time is 10 to 15 minutes.

[0019] Preferably, the pouring temperature is 1400-1420°C.

[0020] Preferably, the amount of silicon-barium-calcium inoculant added is 0.5-0.8% of the weight of the molten iron after melting;

[0021] The amount of silicon-zirconium inoculant added is 0.1-0.15% of the weight of the molten iron.

[0022] The present invention provides an HT350 combined cylinder head casting, which is made from the high silicon-carbon ratio low-alloyed grey cast iron material described in the above technical solution.

[0023] The present invention provides a high silicon-carbon ratio low alloying gray cast iron material, which includes the following components by mass fraction: C 3.00%-3.25%, Si 2.10%-2.50%, Mn0.6%-1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%-0.7%, Cr 0.15%-0.30%, Mo 0.05%-0.20%, Sn0.03%-0.07%, and the balance is Fe. The gray cast iron material composed of the above components and dosage has a high silicon-carbon ratio and low alloying, which improves the mechanical properties of the casting; the high carbon equivalent reduces the shrinkage tendency of the casting. Experimental results show that the tensile strength of the gray cast iron material cast to produce a joint cylinder head (the wall thickness of the sampling part is 20mm-30mm) can reach more than 300MPa, the hardness can reach 200-250HBW, and the shrinkage and water leakage rate of the casting is less than 0.8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The graphite structure and matrix structure of the casting prepared in Example 1 of the present invention;

[0025] Figure 2 The graphite structure and matrix structure of the casting prepared in Example 2 of the present invention;

[0026] Figure 3 The graphite structure and matrix structure of the casting prepared in Example 3 of the present invention;

[0027] Figure 4 The graphite structure and matrix structure (containing a small amount of ferrite) of the casting of Comparative Example 1;

[0028] Figure 5 The graphite structure and matrix structure of the casting of Comparative Example 2. DETAILED DESCRIPTION

[0029] The present invention provides a high silicon-carbon ratio low alloyed HT350 combined cylinder head material, which comprises the following components by mass fraction:

[0030] C 3.00%~3.25%, Si 2.10%~2.50%, Mn0.6%~1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%~0.7%, Cr 0.15%~0.30%, Mo 0.05%~0.20%, Sn0.03%~0.07%, and the balance is Fe.

[0031] The high silicon-carbon ratio low alloyed HT350 conjoined cylinder head material provided by the present invention includes C3.00% to 3.25%, specifically 3.00%, 3.01%, 3.02%, 3.03%, 3.04%, 3.05%, 3.06%, 3.07%, 3.08%, 3.09%, 3.10%, 3.11%, 3.12%, 3.13%, 3.14%, 3.15%, 3.16%, 3.17%, 3.18%, 3.19%, 3.20%, 3.21%, 3.22%, 3.23%, 3.24% or 3.25%.

[0032] The high silicon-carbon ratio low alloyed HT350 combined cylinder head material provided by the present invention includes Si2.10% to 2.50%, specifically 2.10%, 2.15%, 2.20%, 2.25%, 2.30%, .35%, 2.40%, 2.45% or 2.50%.

[0033] Chemical composition directly affects the organizational properties of gray cast iron, among which the selection of carbon and silicon is particularly important; the carbon equivalent of molten iron is 3.85% to 4.15%, which reduces the shrinkage tendency of castings; the increase in carbon equivalent increases the amount of graphite precipitation, ensuring the casting performance of molten iron, but the graphite's splitting effect on the matrix increases, so a higher silicon-carbon ratio plus low alloying is used to improve the mechanical properties of castings. The carbon content is controlled at 3.00% to 3.25%, the silicon content is controlled at 2.10% to 2.50%, and the silicon-carbon ratio is controlled in the range of 0.7 to 0.9; a high silicon-carbon ratio is used to improve the mechanical properties of castings by utilizing the primary austenite dendrite strengthening effect and silicon solid solution strengthening effect.

[0034] The high silicon-carbon ratio low alloyed HT350 combined cylinder head material provided by the present invention includes Mn 0.6% to 1.2%, and the content is specifically 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.1%, 1.15% or 1.2%.

[0035] The high silicon-carbon ratio low alloyed HT350 conjoined cylinder head material provided by the present invention includes 0.07%≤S≤0.13%; the content is specifically 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12% or 0.13%.

[0036] The high silicon-carbon ratio low alloyed HT350 conjoined cylinder head material provided by the present invention includes P≤0.06%, specifically 0.06%, 0.05%, 0.04%, 0.03%, 0.02% or 0.01%.

[0037] The high silicon-carbon ratio low alloyed HT350 combined cylinder head material provided by the present invention comprises 0.3% to 0.7% Cu; the specific content is 0.3%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65% or 0.70%.

[0038] The high silicon-carbon ratio low alloyed HT350 combined cylinder head material provided by the present invention includes Cr0.15% to 0.30%; the content is specifically 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29% or 0.30%.

[0039] The high silicon-carbon ratio low alloyed HT350 combined cylinder head material provided by the present invention includes Mo 0.05% to 0.20%; the content is specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.20%.

[0040] The high silicon-carbon ratio low alloyed HT350 conjoined cylinder head material provided by the present invention comprises Sn 0.03% to 0.07%, and the specific content is 0.03%, 0.04%, 0.05%, 0.06% or 0.07%.

[0041] The high silicon-carbon ratio low alloyed HT350 combined cylinder head material provided by the present invention has a residual content of Fe.

[0042] The alloying elements in the present invention include Cu, Cr, Mo and Sn, which promote graphitization, increase the proportion of matrix pearlite, reduce the spacing between pearlite sheets, refine the pearlite, and improve the mechanical properties of the casting, such as tensile strength.

[0043] In a specific embodiment of the present invention, the composition of the high silicon-carbon ratio low alloyed HT350 conjoined cylinder head material includes: C 3.15%, Si 2.23%, Mn 0.64%, S 0.069%, P 0.022%, Cu 0.45%, Cr 0.28%, Mo0.11%, Sn 0.051%, Ti 0.010%, Al 0.004%, Sb 0.003%, V 0.004%, Pb 0.002%, and the balance Fe;

[0044] Or including C 3.13%, Si 2.34%, Mn 0.67%, S 0.076%, P 0.023%, Cu 0.44%, Cr0.26%, Mo 0.12%, Sn 0.048%, Ti 0.013%, Al 0.005%, Sb 0.002%, V 0.004%, Pb0.002%, and the balance Fe;

[0045] Or include C 3.17%, Si 2.44%, Mn 0.71%, S 0.086%, P 0.024%, Cu 0.45%, Cr0.29%, Mo 0.11%, Sn 0.051%, Ti 0.011%, Al 0.004%, Sb 0.003%, V 0.003%, Pb0.003%, and the balance Fe.

[0046] The present invention provides a method for preparing the high silicon-carbon ratio low alloyed HT350 combined cylinder head material according to the above technical solution, comprising the following steps:

[0047] The recycled materials are melted, silicon carbide, manganese silicon alloy, and scrap steel are added; the carburizer is added in batches, and the iron materials include scrap steel and recycled materials;

[0048] When the weight of the iron material (scrap steel and recycled materials) reaches 75-85% of the full furnace, add ferrosilicon and ferrosulfur, as well as electrolytic copper, ferrochrome, ferromolybdenum and tin particles. After all are melted, heat it to 1450-1500℃, sprinkle in the slag remover to remove the slag, and then heat it up and let it stand;

[0049] After standing, the iron is tapped and silicon-barium-calcium inoculants are added. After the inoculation is completed, the molten iron in the ladle is taken to test the chemical composition. After the chemical composition is qualified, pouring is carried out;

[0050] During the pouring process, silicon-zirconium inoculant is added to perform secondary inoculation to obtain a cast casting, which is then cooled to obtain a high silicon-carbon ratio low-alloyed HT350 combined cylinder head material.

[0051] The present invention melts the recycled materials, adds silicon carbide, manganese silicon alloy, and then adds scrap steel; the carburizer is added in batches with the iron material, and the iron material includes scrap steel and recycled materials. In the present invention, the total amount of recycled materials and scrap steel is 100%, the recycled materials account for 20-30%, and the scrap steel accounts for 70-80%; based on the mass of the iron material, silicon carbide accounts for 1-1.5%, manganese silicon alloy accounts for 0.2-0.4%, and the carburizer accounts for 1.5-2.5%.

[0052] The recycled materials used in the present invention are casting pouring risers and air eye pins produced by Weichai Power Co., Ltd.; the chemical composition thereof includes C 3.00%-3.25%, Si 2.10%-2.50%, Cu 0.3%-0.7%, Cr0.15%-0.30%, Mo 0.05%-0.20%, Sn 0.03%-0.07%, Mn0.6%-1.2%, 0.07%≤S≤0.13%, P≤0.06%, Ti≤0.025%, Al≤0.01%, Sb≤0.004%, V≤0.020%, Pb≤0.004%, and the rest is Fe.

[0053] The present invention preferably adopts a medium frequency induction furnace for molten iron smelting; first, the recycled materials are added into the furnace for melting, and after the recycled materials are added, silicon carbide and manganese silicon alloy are added into the medium frequency induction melting furnace, and then scrap steel is added, and the recarburizer is added into the furnace in batches along with the iron materials (scrap steel and recycled materials), and each time shall not exceed 75kg.

[0054] When the weight of the iron material (scrap steel and recycled materials) reaches 75-85% of the full furnace, ferrosilicon and ferrosulfur are added, as well as electrolytic copper, ferrochrome, ferromolybdenum and tin particles. After all are melted, the temperature is raised to 1450-1500°C, and a slag remover is sprinkled in for slag removal, and then the temperature is raised and allowed to stand. The slag remover is sprinkled in the present invention for one slag removal; the present invention preferably heats to 1530-1550°C for standing, and the standing time is 10-15 minutes. Based on the iron material, ferrosilicon accounts for 1.3-1.6%, and ferrosulfur accounts for 0.1-0.2%.

[0055] In a specific embodiment of the present invention, the charge ratio is 80% scrap steel and 20% recycled materials; based on the total amount of scrap steel and recycled materials as 100%, silicon carbide accounts for 1%, recarburizer accounts for 1.8%, ferrosilicon accounts for 1.3%, manganese silicon alloy accounts for 0.25% and ferrosulfide accounts for 0.15%.

[0056] After standing, the present invention preferably adopts a carbon-sulfur meter and a direct-reading spectrometer to analyze the chemical composition of the molten iron, and adjusts the chemical composition to meet the process requirements: C 3.00%-3.25%, Si 1.80%-2.00%, Mn 0.6%-1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%-0.7%, Cr0.15%-0.30%, Mo 0.05%-0.20%, Sn 0.03%-0.07%.

[0057] The present invention taps the iron after standing, adds silicon-barium-calcium inoculants, takes the molten iron in the ladle to detect the chemical composition after the inoculation is completed, and pours after the chemical composition is qualified. In the process of tapping the iron of the present invention, the silicon-barium-calcium inoculant is added to the molten iron of the ladle along with the funnel, and the amount of the silicon-barium-calcium inoculant added accounts for 0.5% to 0.8% of the mass of the molten iron after melting, and the particle size is 2 to 8 mm. The silicon-barium-calcium inoculant used in the present invention is processed with a high inoculation amount to provide sufficient cores for graphite precipitation and reduce the tendency of molten iron to be overcooled.

[0058] After the inoculation is completed, the molten iron in the ladle is taken to detect the chemical composition, and casting is performed after the chemical composition is qualified. The final chemical composition mass percentage content of the high-strength gray iron casting produced according to the above steps is: C3.00%~3.25%, Si2.10%~2.50%, Mn0.6%~1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%~0.7%, Cr 0.15%~0.30%, Mo 0.05%~0.20%, Sn 0.03%~0.07%, and the balance is Fe and impurity elements.

[0059] In the present invention, silicon zirconium inoculant is added during the pouring process for secondary inoculation to obtain a cast casting, which is cooled to obtain a high silicon-carbon ratio low alloy HT350 combined cylinder head material. The amount of silicon zirconium inoculant added in the present invention is 0.10-0.15% of the weight of the molten iron.

[0060] The pouring temperature of the present invention is 1400-1420° C. After pouring, the casting is preferably cooled in a cooling corridor for more than 4 hours, and then boxed and transferred to cleaning.

[0061] The present invention adopts a primary inoculation in front of the furnace and a secondary inoculation along with the flow, and a high inoculation amount is combined to provide sufficient cores for graphite precipitation.

[0062] The present invention preferably takes the casting body for metallographic structure and mechanical property analysis. The metallographic structure analysis uses a metallographic microscope to analyze the graphite morphology and matrix structure, and the mechanical properties use a universal tensile testing machine to test the tensile strength of the casting, and a Brinell hardness tester to test the hardness of the casting.

[0063] The present invention provides an HT350 combined cylinder head casting, which is made from the high silicon-carbon ratio low-alloyed grey cast iron material described in the above technical solution.

[0064] To further illustrate the present invention, a high silicon-carbon ratio low alloyed gray cast iron material and its preparation method and HT350 combined cylinder head casting provided by the present invention are described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0065] Example 1

[0066] 1) Charge ratio: The charge ratio is 80% scrap steel, 20% recycled material, 1.0% silicon carbide, 1.8% carburizer, 1.3% ferrosilicon, 0.25% manganese silicon alloy, and 0.15% ferrosulfide.

[0067] 2) Melting process: First, add 20% of the recycled materials by weight into the furnace for melting. After the recycled materials are added, add 1.0% silicon carbide and 0.25% manganese silicon alloy into the medium frequency induction melting furnace, and then start to add 80% of the scrap steel by weight. The carburizer is added into the furnace in batches with the iron materials (scrap steel and recycled materials), and each time shall not exceed 75kg. When the weight of the iron materials (scrap steel and recycled materials) reaches about four-fifths of the full furnace, 1.3% ferrosilicon and 0.15% ferrosulphur are added into the furnace. At the same time, 30kg of electrolytic copper, 35kg of ferrochrome, 17kg of ferromolybdenum, and 6kg of tin particles are added into the furnace. After all the iron materials (scrap steel and recycled materials) are melted, the electric furnace is heated to 1480℃, and the slag remover is sprinkled in for a slag removal. The temperature is raised to 1540℃ for high-temperature standing, and the standing time is 10min. The chemical composition of molten iron was analyzed using a carbon-sulfur meter and a direct-reading spectrometer, and the chemical composition was adjusted to meet the process requirements: C 3.15%, Si 1.90%, Mn 0.64%, S 0.069%, P 0.02%, Cu 0.45%, Cr 0.28%, Mo 0.11%, Sn 0.051%, and other elements were Ti 0.010%, Al 0.004%, Sb 0.003%, V 0.004%, Pb 0.002%, and the rest was Fe.

[0068] 3) Inoculation treatment: During the iron-discharging process, silicon-barium-calcium inoculants are added to the molten iron in the ladle along with the funnel flow, and the amount of silicon-barium-calcium inoculants added is controlled to be 0.5%. After the inoculation is completed, the molten iron in the ladle is taken to detect the chemical composition, and only the silicon content is detected. The other components are the same as the components in step 2, so the final chemical composition mass percentage content is: C3.15%, Si 2.23%, Mn 0.64%, S0.069%, P 0.022%, Cu 0.45%, Cr 0.28%, Mo 0.11%, Sn 0.051%. Other elements are Ti0.010%, Al 0.004%, Sb 0.003%, V0.004%, Pb 0.002%, and the rest is Fe.

[0069] 4) In-stream inoculation: Silicon zirconium in-stream inoculation agent is added during the pouring process for secondary inoculation, and the added amount is controlled at 0.10%.

[0070] 5) Cooling and boxing: The pouring temperature is 1410℃. After pouring, the castings are cooled in the cooling corridor for 4.5 hours, and then boxed and transferred to cleaning.

[0071] Example 2

[0072] The difference between this embodiment and embodiment 1 is that the amount of silicon-barium-calcium inoculant added during inoculation is controlled to be 0.65%. The final chemical composition by mass percentage is: C 3.13%, Si 2.34%, Mn 0.67%, S0.076%, P 0.023%, Cu0.44%, Cr 0.26%, Mo 0.12%, Sn 0.048%. Other elements are Ti 0.013%, Al 0.005%, Sb 0.002%, V 0.004%, Pb 0.002%, and the rest is Fe.

[0073] Example 3

[0074] The difference between this embodiment and embodiment 1 is that the amount of silicon-barium-calcium inoculant added during inoculation is controlled to be 0.8%. The final chemical composition by mass percentage is: C 3.17%, Si 2.44%, Mn 0.71%, S0.086%, P 0.024%, Cu0.45%, Cr 0.29%, Mo 0.11%, Sn 0.051%. Other elements are Ti 0.011%, Al 0.004%, Sb 0.003%, V 0.003%, Pb 0.003%, and the rest is Fe.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that no tin particles are added as alloying elements. The final chemical composition by mass percentage is: C 3.18%, Si 2.19%, Mn 0.67%, S 0.078%, P 0.021%, Cu 0.48%, Cr 0.27%, Mo 0.10%. Other elements are Ti 0.010%, Al 0.006%, Sb 0.004%, V 0.003%, Pb 0.002%, and the rest is Fe.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that only one inoculation treatment before the furnace is used, and no inoculation treatment is performed during pouring. The final chemical composition by mass percentage is: C 3.20%, Si 2.21%, Mn 0.68%, S 0.073%, P 0.022%, Cu 0.43%, Cr 0.27%, Mo 0.12%, Sn 0.048%. Other elements are Ti 0.013%, Al 0.005%, Sb 0.002%, V 0.004%, Pb 0.002%, and the rest is Fe.

[0079] The present invention analyzes the mechanical properties of the casting body of the embodiment and the comparative example respectively, and the results are shown in Table 1. It can be seen from the table that the mechanical properties of the embodiment can stably reach 300MPa, the metallographic structure is graphite A type 4, and the pearlite content is greater than 98%. The comparative example cannot stably reach 300MPa, the hardness cannot stably reach 200HBW~250HBW, the metallographic structure is graphite A type 4, but the matrix structure has a small amount of ferrite.

[0080] Table 1 Mechanical properties of castings prepared in Examples and Comparative Examples

[0081]

[0082]

[0083] It can be seen from the above embodiments that the present invention provides a high silicon-carbon ratio low alloying gray cast iron material, which includes the following components by mass fraction: C 3.00% to 3.25%, Si 2.10% to 2.50%, Mn0.6% to 1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3% to 0.7%, Cr 0.15% to 0.30%, Mo 0.05% to 0.20%, Sn0.03% to 0.07%, and the balance is Fe. The gray cast iron material composed of the above components and dosage has a high silicon-carbon ratio and low alloying, which improves the mechanical properties of the casting; the high carbon equivalent reduces the shrinkage tendency of the casting. The experimental results show that the tensile strength of the cylinder head (wall thickness of the sampling part is 20mm-30mm) produced by casting gray cast iron material can reach more than 300MPa, the hardness can reach 200-250HBW, and the shrinkage and water leakage rate of the casting is less than 0.8%.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high silicon-carbon ratio low alloy gray cast iron material, comprising the following components by mass fraction: C 3.00%~3.25%, Si 2.10%~2.50%, Mn0.6%~1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu 0.3%~0.7%, Cr 0.15%~0.30%, Mo 0.05%~0.20%, Sn0.03%~0.07%, and the balance is Fe.

2. The high silicon-carbon ratio low alloy material according to claim 1, characterized in that: The silicon-carbon ratio is 0.7 to 0.

9.

3. The high silicon-carbon ratio low alloy material according to claim 1, characterized in that: The molten iron carbon equivalent of the cylinder head material is 3.85-4.15%.

4. A method for preparing the high silicon-carbon ratio low alloyed grey cast iron material according to any one of claims 1 to 3, comprising the following steps: The recycled materials are melted, silicon carbide, manganese silicon alloy, and scrap steel are added; the carburizer is added in batches along with the iron materials, and the iron materials include scrap steel and recycled materials; When the weight of the iron material reaches 75-85% of the full furnace, add ferrosilicon and ferrosulfur, as well as electrolytic copper, ferrochrome, ferromolybdenum and tin particles. After all are melted, heat it to 1450-1500℃, sprinkle in the slag remover to remove the slag, and then heat it up and let it stand; After standing, the iron is tapped and silicon-barium-calcium inoculants are added. After the inoculation is completed, the molten iron in the ladle is taken to test the chemical composition. After the chemical composition is qualified, pouring is carried out; During the pouring process, silicon-zirconium inoculant is added to perform secondary inoculation to obtain a cast casting, which is then cooled to obtain a low-alloy gray cast iron material with a high silicon-carbon ratio.

5. The preparation method according to claim 4, characterized in that: The chemical composition of the molten iron after standing is: C 3.00%~3.25%, Si 1.80%~2.00%, Mn 0.6%~1.2%, 0.07%≤S≤0.13%, P≤0.06%, Cu0.3%~0.7%, Cr 0.15%~0.30%, Mo 0.05%~0.20%, Sn0.03%~0.07%.

6. The preparation method according to claim 4, characterized in that: The particle size of the silicon-barium-calcium inoculant is 2 to 8 mm; The particle size of the silicon-zirconium inoculant is 0.15-0.7 mm.

7. The preparation method according to claim 4, characterized in that: Then raise the temperature to 1530-1550℃ and let it stand; The standing time is 10 to 15 minutes.

8. The preparation method according to claim 4, characterized in that: The pouring temperature is 1400-1420°C.

9. The preparation method according to claim 4, characterized in that: The amount of silicon-barium-calcium inoculant added is 0.5-0.8% of the weight of the molten iron; The amount of silicon-zirconium inoculant added is 0.1-0.15% of the weight of the molten iron.

10. An HT350 combined cylinder head casting, made from the high silicon-carbon ratio low alloyed grey cast iron material according to any one of claims 1 to 3.